1992
DOI: 10.1037/h0078693
|View full text |Cite
|
Sign up to set email alerts
|

The research base, psychometric properties, and clinical uses of the MMPI-2 and MMPI-A.

Abstract: The Minnesota Multiphasic Personality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The MMPI–2 was a modest, incremental revision of the original MMPI which, as reflected in the name of the effort that produced it, the MMPI Restandardization Project, focused primarily on replacing the 1940s test norms. It was positioned as a replacement of the MMPI, and the training and marketing effort focused on “continuity.” For example, Butcher and Pope (1992) noted that the MMPI–2 developers took a “conservative” approach to the revision, opting to “maintain the continuity of the original validity and clinical scales by keeping them intact, that is, comprising the same items as the original scales” (p. 63). In contrast, the MMPI–2–RF is the product of an effort to modernize these 70-year-old MMPI scales, representing a paradigm shift.…”
Section: Comparison Of Mmpi–2 and Mmpi–2–rf Adoption Rates Lacks Contextmentioning
confidence: 99%
“…The MMPI–2 was a modest, incremental revision of the original MMPI which, as reflected in the name of the effort that produced it, the MMPI Restandardization Project, focused primarily on replacing the 1940s test norms. It was positioned as a replacement of the MMPI, and the training and marketing effort focused on “continuity.” For example, Butcher and Pope (1992) noted that the MMPI–2 developers took a “conservative” approach to the revision, opting to “maintain the continuity of the original validity and clinical scales by keeping them intact, that is, comprising the same items as the original scales” (p. 63). In contrast, the MMPI–2–RF is the product of an effort to modernize these 70-year-old MMPI scales, representing a paradigm shift.…”
Section: Comparison Of Mmpi–2 and Mmpi–2–rf Adoption Rates Lacks Contextmentioning
confidence: 99%
“…A number of excellent examples of this approach exist, and certainly, these measures have allowed much quicker progress in our understanding of adolescent PD than sole reliance on developmentally bottom‐up PD measures (i.e., measures that were empirically derived based on child and adolescent data) would have allowed. The most prominent examples of this include the adolescent version of the Minnesota Multiphasic Personality Inventory (MMPI‐A; Butcher & Pope, ; Sellbom & Jarrett, ), the youth version of the Schedule for Nonadaptive and Adaptive Personality (SNAP‐Y; Linde, Stringer, Simms, & Clark, ), and the adolescent version of the Dimensional Assessment of Personality Pathology (DAPP‐BQ‐A; Tromp & Koot, ). These measures were largely based on their adult counterparts, although in all cases modifications were made based on developmental considerations, including readability of items and the developmental appropriateness of various behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Butcher, 1996;Butcher & Pope, 1992) found that to use the norms of the country where the instrument will be applied assures the adequate functioning of the instrument.…”
Section: Discussionmentioning
confidence: 98%
“…The sample consisted of 2600 individuals (1462 women and 1138 men) representative of the North American population in most of the variables according to the 1980 Census (Butcher & Pope, 1992).…”
Section: Participantsmentioning
confidence: 99%